Pathogen Trojan Horse Delivers Bioactive Host Protein to Alter Maize Anther Cell Behavior in Situ. Issue 3 (15th February 2018) - van der Linde, Karina; Timofejeva, Ljudmilla; Egger, Rachel L.; Ilau, Birger; Hammond, Reza; Teng, Chong; Meyers, Blake C.; Doehlemann, Gunther; Walbot, Virginia
Abstract : Maize ZmMAC1 protein delivered to the apoplast by the smut pathogen Ustilago maydis cell-autonomously corrects both somatic cell division and differentiation defects in Zm mac1-1 mutant anthers. Abstract: Small proteins are crucial signals during development, host defense, and physiology. The highly spatiotemporal restricted functions of signaling proteins remain challenging to study in planta. The several month span required to assess transgene expression, particularly in flowers, combined with the uncertainties from transgene position effects and ubiquitous or overexpression, makes monitoring of spatiotemporally restricted signaling proteins lengthy and difficult. This situation could be rectified with a transient assay in which protein deployment is tightly controlled spatially and temporally in planta to assess protein functions, timing, and cellular targets as well as to facilitate rapid mutagenesis to define functional protein domains. In maize ( Zea mays ), secreted ZmMAC1 (MULTIPLE ARCHESPORIAL CELLS1) was proposed to trigger somatic niche formation during anther development by participating in a ligand-receptor module. Inspired by Homer's Trojan horse myth, we engineered a protein delivery system that exploits the secretory capabilities of the maize smut fungus Ustilago maydis, to allow protein delivery to individual cells in certain cell layers at precise time points. Pathogen-supplied ZmMAC1 cell-autonomously corrected both somatic cell division and differentiation defects in mutant Zm mac1-1 anthers. These results suggest that exploiting host-pathogen interactions may become a generally useful method for targeting host proteins to cell and tissue types to clarify cellular autonomy and to analyze steps in cell responses.